Uncertainty Regarding the Limits of the Authority of the Notary Honorary Council and Its Implications for Criminal Law Enforcement - E Ellyza; Natsir Asnawi (Indonesian Journal Publisher, 2026)
Article 66 of the Notary Law grants the Notary Honorary Council an important role in the mechanism for summoning and examining notaries by law enforcement officials. This regulation is intended to protect the position of notaries as public officials exercising state authority in the civil sector. However, the formulation of the norms in Article 66 indicates a lack of clarity regarding the limits of the Notary Honorary Council's authority, particularly regarding the scope of assessments that can be performed in granting approvals. This lack of clarity creates a vague norm that has implications for legal uncertainty and the potential for overlapping authority between the Notary Honorary Council and law enforcement officials in criminal proceedings. This study aims to analyze the provisions on the authority of the Notary Honorary Council in Article 66 of the Notary Law and the implications of this unclear norm on the protection of the notary's position and the effectiveness of criminal law enforcement. The research method employed is normative legal research with a statutory and conceptual approach. The results show that the absence of clear normative parameters in Article 66 leaves a space for diverse interpretations and has the potential to hinder the investigation process, while weakening the legal protection that should be provided to notaries. This situation reflects the unbalanced position between the interests of protecting one's position and the principle of due process of law. This study recommends reformulating Article 66 of the Notary Law by clarifying the limits of the Notary Honorary Council's authority and harmonizing this norm with the criminal justice system.